THEMATIC ASPECTS OF EPISTOLARY DIALOGUES BETWEEN YURII SHEVELIOV AND OLEKSA IZARSKYI - Руднянин, О. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article is dedicated to the study of Yurii Volodymyrovych Sheveliov’s private letters to Oleksa Hryhorovych Izarskyi. It describes main thematic aspects of their correspondence. Due to Yurii Sherekh’s letters and Oleksa Izarskyi’s diaries the author makes an attempt to analyze the epistolary of every writer as a component part of the “integral text”. The paper defines the role of studied epistolary inheritance in the process of Ukrainian literature history development, and also the place of Y. Sheveliov’s private correspondence in further thorough research of life and work of less known Ukrainian writer, literary critic, translator – Oleksa Izarskyi.